Penyampaian Produk Politik Calon Presiden dalam Kontes Pilpres 2024 - Nurmandi, Achmad; Rafi, Sharin Atika; Fridayani, Helen Dian (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
The implementation of elections is a forum for democracy that requires community participation. Community involvement in the election is motivated by the political campaign strategy implemented by the candidates. In the 2024 election, three candidates with their uniqueness will compete in the presidential election. The purpose of this research is to find out the political campaign strategy of each candidate through the perspective of political product delivery in the 2024 presidential election. The data collection technique was carried out using mass media, which was determined by the purposive sampling technique using three main criteria so that as many as 60 news articles were obtained. The data analysis technique uses an interactive model with the stages of data reduction, data presentation, verification, and conclusion drawn. The results of the study show that each candidate uses the same strategy in conducting political campaigns. The three candidates used to push marketing, pull marketing, and pass marketing strategies in political campaigns. However, each candidate uses a different dominant strategy in conveying his political products. The delivery of political products by each candidate also has different activities in their strategy to attract the attention of the public so that they can vote for a certain candidate. This research is limited to the use of data only in the form of online mass media and scientific articles. Further research can use primary data by developing new research in the form of the role of political product delivery and the number of votes obtained in the presidential election.